Microbial cycling, migration and leakage of light alkanes in the Nile Delta Tertiary fan. (November 2020) - Böker, U.; Dodd, T.A.; Goldberg, T.; Aplin, A.C.
Abstract: We present a geochemical dataset which helps unravel the complex set of processes by which light alkanes are sourced, charged, mixed, leaked and altered in the Plio-Pleistocene Nile Delta. Thermogenic gas derives from a sub-Messinian source and mixes with microbial, hydrogenotrophic, methane-rich gas in the Plio-Pleistocene section. There is strong isotopic evidence for both microbial generation and microbial degradation of ethane and propane, but these signals are only recorded where the rates of biological processes outstrip the rate of thermogenic charge. High resolution gas geochemistry profiles through four, 500–1100 m sequences of mixed channel, channel levee, mass flow deposits and hemipelagites shed light on migration and leakage pathways. We see limited geochemical evidence for migration along or across faults which cross-cut mud-rich sequences. Lateral migration along sands/silts delivers gas to structural highs, where leakage occurs vertically along focussed pathways through heterogeneous mud-rich sediments. We propose that in situ generation of microbial gas within mud-rich sequences facilitates percolation of migrating gases that replenishes C2+ components and sustains the biodegradation pathway in syntrophic microbial communities. High resolution changes in gas composition suggest an unequilibrated system which is being actively charged. In some structures, rates of charge and of microbial alteration of gas are broadly similar; in others, rates of charge exceed rates of microbial alteration. Our results have important implications for the understanding of both basin-wide fluid flow and the ecology of the deep biosphere. Highlights: Methane in Pliocene gas accumulations is largely of secondary microbial nature. Microbes in the Nile Delta recycle C2+ alkanes arriving from sub-Messinian sources. Ethane δ 13 C response is buffered unless metabolic rates outpace thermogenic charge. Biodegradation pathways are sustained by percolation of C2+ components.